METAL-INDUCED PROTEIN DENATURATION: REGULARITIES, PATHOLOGICAL MANIFESTATIONS, AND IN VITRO MODELING - Popovych, Tetiana; Kizim, Yaroslav; Obernikhina , Natalia; Voroshylova , Natalia (The Ukrainian Scientific Medical Youth Journal, 2021)
the ability of various metal ions to form complexes with proteins leads to the denaturation of the latter and the development of immune response. Such hapten effects cause the well-known phenomenon of nickel-allergic contact dermatitis. No less typical are side effects of gadolinium compounds, that are used as contrasts for magnetic resonance imaging, but cause the development of fibrosis. In both cases an important role belongs to the interaction of metal ions with collagen structures. The aim of our study was to compare in vitro effects of copper and nickel ions on destabilized products of collagen cleavage. Significant difference between these metals in their ability to induce aggregation at close to physiological pH values was shown. The influence on the aggregative process of the acidification of the medium was revealed. It was shown that destabilization of protein structure leads to the formation of highly stabilized β-stacked protein aggregates. Comparison of the obtained experimental data with the literature ones makes it possible to approach the understanding of individual mechanisms of toxic effects of metal ions on the human body.